The Effects of the Dynamic Pre-shot Program on Physical Fitness and Golf Performance in Middle-aged Female Golfers - Hyun-Hee Lee; Keun-Ok An; Kwang-Jin Lee (The Asian journal of kinesiology, 2025)
OBJECTIVES This study aimed to investigate the effects of the dynamic pre-shot program on physical fitness and golf performance of middle-aged female golfers. METHODS Thirty-two middle-aged female golfers from S Golf Club were selected for the study and divided into two groups: the dynamic pre-shot program group (DPPG, n=16) and the control group (CG, n=16). Baseline and post-intervention measurements included body composition, physical fitness (muscle strength, flexibility, dynamic balance), and golf performance (carry distance, ball speed, clubhead speed, smash factor). RESULTS The results of this study showed that the dynamic pre-shot program positively improved lateral flexibility, hip rotation, ball speed in both the iron and driver swings, smash factor in both the iron and driver swings, and carry distance in the driver swing among middle-aged female golfers. CONCLUSIONS The dynamic pre-shot program was found to have positive effects on the physical fitness and golf performance of middle-aged female golfers. Therefore, the dynamic pre-shot program is considered effective for improving the physical fitness of middle-aged female golfers and has a positive impact on ball speed, smash factor, and carry distance as their physical fitness improves. KCI Citation Count: 0